2010
DOI: 10.4049/jimmunol.1000082
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Human FOXP3 Target Genes in Natural Regulatory T Cells

Abstract: Material Supplementary 2.DC1http://www.jimmunol.org/content/suppl/2010/06/16/jimmunol.100008

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 129 publications
(169 citation statements)
references
References 88 publications
7
162
0
Order By: Relevance
“…Type 1 diabetes is an example of a disease which arises as a result of complex interactions between genetic and environmental factors conspiring to drive disease progression. A meta‐analysis of six genome‐wide association studies to identify single nucleotide polymorphisms that track with type 1 diabetes identified 45 loci,27 and using our FOXP3 ChIP data,28 we observed that 34 (75%) contain a FOXP3 binding site. A more recent fine mapping of genetic risk of type 1 diabetes identified 51 distinct loci, of which 34 mapped to a gene 29.…”
Section: Treg and Diseasementioning
confidence: 74%
See 4 more Smart Citations
“…Type 1 diabetes is an example of a disease which arises as a result of complex interactions between genetic and environmental factors conspiring to drive disease progression. A meta‐analysis of six genome‐wide association studies to identify single nucleotide polymorphisms that track with type 1 diabetes identified 45 loci,27 and using our FOXP3 ChIP data,28 we observed that 34 (75%) contain a FOXP3 binding site. A more recent fine mapping of genetic risk of type 1 diabetes identified 51 distinct loci, of which 34 mapped to a gene 29.…”
Section: Treg and Diseasementioning
confidence: 74%
“…As well as identifying a significant number of loci both directly bound by FOXP3 and associated with differentially expressed genes in Treg, many loci were identified that are either too far from a transcription start site to annotate to a target gene easily, or do not appear to be associated with differentially expressed genes in Treg. For example, in our human FOXP3 ChIP data set, of almost 3000 FOXP3‐bound regions, only 750 were also annotated to genes differentially expressed in human Treg28 (Figure 1). This has revealed a core network of genes that are tightly regulated by FOXP3 and has also identified significant bioinformatic limitations in annotation of FOXP3‐bound regions.…”
Section: Transcriptional Control Of Treg Formation and Functionmentioning
confidence: 99%
See 3 more Smart Citations